Implementasi Wireless Sensor Network Pada Keamanan Rumah Menggunakan Sensor Pir - Muhammad Risyat Nashrullah; Rakhmadhany Primananda; Edita Rosana Widasari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Home security is a matter of privacy, many people keep property at home. Many criminal acts and increasing from year to year make people become uneasy. One such crime is theft in a house left behind by the inhabitants. To overcome the crime of theft is needed a security system in an empty house. However, home security systems made so far still have many drawbacks such as, security is only focused on one point, security guard rental to keep the house at risk of theft with violence, installing CCTV at risk of the perpetrator can damage CCTV so difficult in observation. Wireless Sensor Network (WSN) is an embedded system equipment in which there is one or more sensors and equipped with communication system equipment. By utilizing WSN technology can be made home security system that can monitor many points and communication between points done wirelessly. Transceiver module used in this research is wifi module ESP8266 and protocol that used is Hypertext Transfer Protocol (HTTP). Based on the results of tests conducted on wireless delivery has a success rate of 100% at a distance of 5 meters between the point of installation of sensors with human objects, and at a distance of 6 meters sensors can detect but has a success rate of 70%. Based on the results of testing the system as a whole, the system can be controlled and provide reports through android applications online with a success rate of 100%.